Research Competency Needs of University Students: Baseline for Research Manual Formulation - Quintos, Jr., Romeo; Pecson, Ryan (Edupedia Publisher, 2026)
Purpose – This study describes and analyzes the research competency needs of college students in a state university in the Philippines. The research intends to inform the formulation of a research manual for higher education institutions. Methodology – The study employed a descriptive, quantitative design using a researcher-developed survey questionnaire (eight domains) that was validated (CVI=1.00) and tested for reliability (α=0.963). One hundred fifty (150) selected student-researchers, acting as leaders and members, participated in the survey process. The said respondents were selected using a simple random sampling technique. Stringent research protocols and ethical considerations were strictly followed. Data from the survey were analysed using descriptive statistics (i.e., mean and standard deviation) and inferential statistics, such as the Kruskal-Wallis (H) test for the non-normal data analysed. Findings – The results reveal that the student-researchers have the highest research competency needs. Moreover, there is no variation in their research competency needs (p<0.05), indicating a statistically identical highest level of need to improve their research competencies. At the outset, a research manual was developed to complement the proposed research policy on standardizing the research format and addressing the research competency needs of university students. Novelty – The development research manual, as an output of the study, provides an innovative way to contextualize instruction and foster creative thinking and innovative solutions to real-life academic and societal problems. Significance – The findings serve as a valuable reference for using research-based competency needs assessment to foster innovation in research practices.